Health-Related Quality of Life of Older Adults in Costa Rica as Measured by the Short-Form-36 Health Survey - Valdivieso Mora, Esmeralda (2018)
Objective: To test the validity of a common measure of health-related quality of life (Short-Form-36 [SF-36]) in cognitively healthy older adults living in rural and urban Costa Rica. Method: Confirmatory factor analysis was applied to SF-36 data collected in 250 older adults from San Jose and Guanacaste, Costa Rica. Results: The best fitting model for the SF-36 was an eight first-order factor structure. A high correlation between the Mental Component Summary and Physical Component Summary scores was found. Region differences indicated that rural dwellers perceive a poorer health-related quality of life compared with the urban group. Discussion: Costa Rican older adults perceived health as a unidimensional construct. Age and urbanity of older adult Costa Ricans should be appreciated when trying to measure self-reported physical and mental health. Cultural context of the individuals should be considered when studying health-related quality of life.